Сучасний стан та перспективи збереження і розвитку ділянки “Розоцвіті” у Національному ботанічному саду ім. М.М. Гришка НАН України - Trofimenko, N.M.; Babytskiy, A.I.; Chernyshov, O.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2010)
The data about taxonomic structure of Rosales plot, modern condition of plants, measures of introduced plants conservation and perspectives of this collection development are given.